Home financing pricing issues in the Bay' Bithaman Ajil (BBA) and Musharakah Mutanaqisah (MMP) - Syahidawati Hj. Shahwan; Mohammad M.O.; Rahman Z.A. (Kolej University Islam Sultan Azlan Shah, 2024)
Indexed by WOS/ Scopus